Increasing Relevance and Applicability of Translation Studies in Bangladesh: From University Students’ Perspectives - Hossain, S. M. Sabbih; Johora, Lailatuz (Innovare Journal of Education, 2024)
This study explores the increasing relevance and applicability of translation studies in Bangladesh, focusing on university students’ perspectives. As globalization and technological advancements blur cultural boundaries, the demand for proficient translation has surged. This research investigates the current state of translation studies in Bangladeshi universities and its potential to enhance graduates’ career prospects. Through qualitative and quantitative methods, including focus group discussions (FGD) and surveys, the study reveals a growing awareness and interest in translation studies among students. Findings indicate a positive outlook on the discipline’s future, highlighting the need for improved curriculum and training programs. The study underscores the importance of translation in bridging cultural gaps and its potential to contribute significantly to the job market in Bangladesh.